2020
DOI: 10.1038/s41598-020-58339-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of Receptor activator of nuclear factor-κB expression in Circulating Tumor Cells during Denosumab predict treatment effectiveness in Metastatic Breast Cancer

Abstract: Receptor-activator of nuclear-factor-κB-ligand (RANKL) and its receptor RANK have been recently identified as key players in breast cancer bone metastases. Since Circulating Tumor Cells (CTCs) are considered a crucial step of metastatic process, we explored RANK expression on CTCs in metastatic breast cancer (MBC), and the predictive value of RANK-positive CTCs in monitoring patients during treatment with denosumab (anti-RANKL antibody). To this purpose, we developed a novel CTC assay to quantify RANK-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
(55 reference statements)
2
21
0
Order By: Relevance
“…Moreover, to investigate the co-expression of both epithelial and mesenchymal markers in CTCs of pediatric sarcomas, we used the anti-Desmin Ab (clone Y66; abcam, UK), in conjunction with the CTC standard assay, as previously reported for other integrated tests [ 25 , 26 ]. Results were expressed as the total number of CTCs and Desmin-positive CTCs per 7.5 ml of blood.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, to investigate the co-expression of both epithelial and mesenchymal markers in CTCs of pediatric sarcomas, we used the anti-Desmin Ab (clone Y66; abcam, UK), in conjunction with the CTC standard assay, as previously reported for other integrated tests [ 25 , 26 ]. Results were expressed as the total number of CTCs and Desmin-positive CTCs per 7.5 ml of blood.…”
Section: Methodsmentioning
confidence: 99%
“…Today, breast cancer patients with bone metastases are treated with denosumab, an inhibitory antibody targeting RANKL. Recently, Pantano et al showed that RANK-expressing CTCs were present in blood from breast cancer patients with skeletal metastases [ 50 ]. Moreover, the presence of RANK-positive CTCs was associated with an increased response to denosumab treatment.…”
Section: Liquid Biopsies On Breast Cancermentioning
confidence: 99%
“…The presence of CTCs increases the risk of metastasis, and higher numbers of CTCs are inversely associated with progression-free survival and overall survival in patients with breast cancer [ 12 , 14 , 15 ]. CTCs have been suggested as a prognostic tool for monitoring metastasis or the efficacy of chemotherapy [ 16 , 17 , 18 , 19 ]. Studies have shown that potential diagnostic biomarkers representing stemness [ 20 ], immunogenic CTC [ 18 ], and signaling molecules that promote breast cancer metastasis [ 19 ] are found in CTCs.…”
Section: Breast Cancer and Circulating Tumor Cellsmentioning
confidence: 99%
“…CTCs have been suggested as a prognostic tool for monitoring metastasis or the efficacy of chemotherapy [ 16 , 17 , 18 , 19 ]. Studies have shown that potential diagnostic biomarkers representing stemness [ 20 ], immunogenic CTC [ 18 ], and signaling molecules that promote breast cancer metastasis [ 19 ] are found in CTCs. The mutation and expression levels of breast cancer-associated genes such as BRCA 1/2 are also detectable by liquid biopsy [ 15 , 21 ].…”
Section: Breast Cancer and Circulating Tumor Cellsmentioning
confidence: 99%